Mortality Prevention in Pregnancy With Pulmonary Arterial Hypertension - Olivia Handayani; Mohammad Saifur Rohman; Ardian Rizal; Setyasih Anjarwani (Heart Science Journal, 2020)
Background : Pulmonary hypertension (PH) is a global disease that affects all age groups and progresses in later years. Pregnancy with PH has a poor prognosis, and it is because of delayed diagnosis or even undiagnosed. PH gives high-risk to the mother and fetus; therefore, arranging a multidisciplinary team for pregnancy and delivery management is required.Objective : This case report was structured to emphasize mortality prevention in pregnancy with PH.Case : A 23-year-old female was admitted to the hospital with a chief complaint of dyspnea at rest. She was 34-week pregnant pregnancy and previously had a history of abortion with similar symptoms. After conducting some examinations, the patient was diagnosed with pulmonary hypertension. We planned for lung maturation for the fetus, scheduled termination, delivery method, and post-delivery care. The fetus was dead intra-uterine on day 5 of care, and the mother passed away 24 hours later.Conclusion : In summary, pregnancy was not advised in women with pulmonary hypertension. The collaboration and management by a multidisciplinary team are essential to improve outcomes if the pregnancy was still wanted.